AB0146 Self-Reactive IGE Exacerbates Interferon Responses Associated with Autoimmunity. (15th July 2016) - Sanjuan, M.A.; Henault, J.; Riggs, J.; Karnell, J.L.; Liarski, V.; Shirinian, L.; Xu, L.; Casey, K.; Smith, M.A.; Khatry, D.; Clarke, L.; Herbst, R.; et al.
Abstract : Background: The discovery of Immunoglobulin E (IgE) nearly 40 years ago was a breakthrough in the field of allergy research. IgE directed against parasitic worms and allergens binds mast cells and basophils, triggering an inflammatory response that is characterized by the release of histamine and Th2 cytokines. Here we report that double-stranded DNA (dsDNA)-specific IgE autoantibodies complexed to DNA activate plasmacytoid dendritic cells (pDC), an immune cell type linked to viral defense, leading to the secretion of substantial amounts of IFN-a. Although typical IgE mediated responses are not a hallmark of systemic lupus erythematosus (SLE), IFN-a producing pDCs are a key driver for loss of immune tolerance to host DNA in SLE. We, therefore, investigated this apparent paradox and found that even the small concentrations of circulating dsDNA-specific IgE found in SLE patients greatly potentiated pDC secretion of IFN-a by triggering phagocytosis via the Fc-epsilon receptor I (FceRI) and TLR9-mediated DNA sensing in the phagolysosome. Consequently, this potent pDC signaling mechanism reduces the threshold of pDC activation, which has the potential to expand anti-DNA responses and greatly exacerbate self-inflicted damage. These findings expand the known pathogenic mechanisms of IgE mediated inflammation beyond those found in allergies and demonstrate that, in addition to recognizing exogenous allergens, IgE can also bind to autoantigens and drive an aberrant and self-destructive anti-viral response. This previously unrecognized link between IgE and the interferon pathway provides additional insights into the pathological mechanisms underlying autoimmunity and may be useful in the rational design of therapies for the treatment of diseases such as SLE. Disclosure of Interest: M. Sanjuan Employee of: Medimmune, J. Henault Employee of: Medimmune, J. Riggs Employee of: Medimmune, J. Karnell Employee of: Medimmune, V. Liarski: None declared, L. Shirinian Employee of: Medimmune, L. Xu Employee of: Medimmune, K. Casey Employee of: Medimmune, M. Smith Employee of: Medimmune, D. Khatry Employee of: Medimmune, L. Clarke Employee of: Medimmune, R. Herbst Employee of: Medimmune, R. Ettinger Employee of: Medimmune, M. Petri: None declared, M. Clark: None declared, T. Mustelin Employee of: Medimmune, R. Kolbeck Employee of: Medimmune